Kontribusi Daya Ledak Otot Tungkai Terhadap Hasil Lari Jarak Pendek Mahasiswa Penjaskesrek Universitas Islam Indragiri - Pratama, Tommy (Jurnal Edukasi, 2023)
The problem in this research is that the physical elements of several semester 4 students of Penjaskesrek, Indragiri University are still not optimal, such as student balance that is not optimal which causes students to get out of the running track line or touch their running partners. Then the explosive power of the student's leg muscles is also not optimal, as a result the student does not get good propulsion when starting the 100 meter run. Then the coordination of motion is also not optimal so that it has an impact on the results of student running which is slowed down, then the endurance of the student's leg muscles is still not optimal, this can be seen from the lack of increase in student speed to the finish line. The purpose of this study was to determine the Contribution of Limb Muscle Explosive Power to the Short Distance Running Results of Penjaskesrek Students Batch 2022 at Indragiri Islamic University.The type of this research is correlation. The population and sample in this study were Semester 4 Students of Penjaskesrek Class of 2022 at Indragiri Islamic University, totaling 15 people. The research instrument used was the standing broadjump test and short distance running. The data analysis technique used is the correlation value test. Based on the results of the research that has been done, the following conclusions can be drawn: There is a Contribution of Explosive Power of the Leg Muscles to the Short Distance Running Results of Physical Education, Health and Recreation Students of the Islamic University of Indragiri by 63.36% with a value of rcount = 0.796 > rtable = 0.514 and tcount = 4.73 > ttable = 1.771.